Factors That Influence The Intention To Uset Certified Mustard Oil Seedst On Smallholders Estate (Study On Oil Palm Farmers In Aek Kuasan District Asahan Regency North Sumatra ) - Nasution, Myrna Pratiwi; Fauzi, Ahmad (Agriprimatech, 2025)
This research aims to analyze the use of certified oil palm seedlings in smallholder plantations in Aek Kuasan District, Asahan Regency, North Sumatra. The model used to explain the use of certified oil palm seedlings is the theory of planned behavior (TPB) with variables of attitude, subjective norms and perception of behavioral control. The method used to test the pattern of correlation relationships of variables is Multiple Linear Analysis using SPSS 22.0. The data of this study are primary data obtained using a questionnaire. Based on the results of regression and data analysis using the t-test, the t value of the attitude variable is 3.065 and the variable of perception of behavioral control is 3.170 greater than t Table 1.984 has a positive and significant effect on the intention to use certified oil palm seedlings, while the t value of the subjective norm variable is 1.403 smaller than t table 1.984 does not have a significant effect on the intention of farmers to use certified oil palm seedlings. The results of the determination coefficient test (R2) show that the variables of attitude, subjective norms, and perception of behavioral control can explain the dependent variable, namely farmers' intentions, by 38.7% and the remaining 61.3% is explained by other variables outside the model. Simultaneous testing uses the f test where the f count value of 20.217 is greater than the f table value of 2.47. This means that simultaneously the variables of attitude, subjective norms, and perception of behavioral control have a significant effect on farmers' intentions to use certified oil palm seeds in Aek Kuasan District, Asahan Regency, North Sumatra.